2014
DOI: 10.1007/s12032-014-0281-4
|View full text |Cite
|
Sign up to set email alerts
|

The preliminary study of p53 codon 72 polymorphism and risk of cervical carcinoma in Gabonese women

Abstract: Cervical cancer is the leading cause of cancer-related death in Africa and the first most common cancer in Gabonese women due to infection of high-risk human papillomavirus (HPV). However, other cofactors such as genetic factors also come into play. A common polymorphism of the p53 codon 72 in exon 4 with two alleles encoding arginine or proline is known at this locus. The homozygous arginine form of this polymorphism has been associated with the development of cervical cancer as an increased genetic risk fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Some studies claimed that this SNP is a risk factor for oral cancer while other studies detected no effect in oral carcinogenesis, showing clear discrepancy between results across the world. The different patterns noticed in allelic distribution and genotypic frequencies of this polymorphism may be due to variations in methodological approaches, sample size, laboratory performance, DNA quality and source, variation in ethnic background or environmental exposures of study populations [16,32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies claimed that this SNP is a risk factor for oral cancer while other studies detected no effect in oral carcinogenesis, showing clear discrepancy between results across the world. The different patterns noticed in allelic distribution and genotypic frequencies of this polymorphism may be due to variations in methodological approaches, sample size, laboratory performance, DNA quality and source, variation in ethnic background or environmental exposures of study populations [16,32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Additional studies also reported the potential roles of common gene variants that are involved in the cellular cycle and apoptosis, cell proliferation and differentiation, DNA repair, and immune responses [40][41][42][43][44][45][46]. Nevertheless, as in many other association analyses, evidence of how genetic susceptibility is linked mechanistically to the progression of cervical cancer is still lacking.…”
Section: Key Factors That Contribute To Hpv Persistence and Cervical mentioning
confidence: 99%
“…Previous studies have investigated this association in the SSA, and the results reported thus far have been inconclusive [16‐25]. The inconclusive findings may be due to the small sample sizes, which reduce the statistical power of these studies to detect a small genetic effect.…”
Section: Introductionmentioning
confidence: 99%